Differential diagnosis of orf viruses by a single-step PCR - Chan, Kun-Wei; Hsu, Wei-Li; Wang, Chi-Young; Yang, Cheng-Hsiung; Lin, Fong-Yuan; Chulakasian, Songkhla; Wong, Min-Liang (Journal of virological methods, 2009)
The complete nucleotide sequence of the A32L gene (named after vaccinia virus, corresponding with open reading frame 108 of the orf virus and encoding an ATPase) of the orf virus was studied using samples of orf virus from infected goats, which were collected from six outbreaks in central Taiwan. DNA sequence analysis of the A32L genes of these and isolates from other countries showed sequence heterogeneity (base pair variation and deletion) in the 3′-terminal regions. This finding led to the development of a polymerase chain reaction (PCR) method for the rapid differential diagnosis of orf virus infections, and the results demonstrated that this was an easy and reliable method for genotyping of orf viruses.